Волоська слобода Старокиївської гори - Климовський, С.І.; Мовчан, І.І.; Рєутов, А.В. (Археологія, 1996)
У статті публікуються матеріали розкопок пізньосередньовічних об'єктів по вул. Велика Житомирська, 11 у Києві. Дані розкопок дозволили підтвердити існування на Старокиївській горі на рубежі XVII—XVIII ст. Волоської слободи, населеної вихідцями з Молдови. В статье публикуются материалы раскопок позднесредневековых объектов по ул. Болыная Житомирская, 11 в Киеве. Данные раскопок позволили подтвердить существование на Старокиевской горе на рубеже XVII—XVIII вв. Волошской слободы, заселенной выходцами из Молдовы. Благодаря раскопкам четко зафиксированы наземные постройки,с подвалами, реконструкция которых позволила восстановить внешний вид деревянной застройки Киева этого времени. Обращают на себя внимание также находки строительных жертв. The paper presents findings of excavations of late medieval objects in Bolshaya Zhitomirskaya Sir., 11 in Kyiv. The findings have permitted substantiating the existence of the Voloshian settlement inhabited by the Moldovians by birth on the Starokicvskaya hill between the 17th and 18th centuries. The excavations made it possible to identify distinctly overground structures with cellars. Their reconstruction contributed much to the restoration of the appearance of the wooden buildings in Kyiv at that time. Findings of victims of building are also of significant interest.